Geomechanical parameters updating in an underground work - Miranda, Tiago F. S. (2007)
In geotechnical engineering, and in the particular case of underground works, a great number of uncertainties arise due to the lack of knowledge of the involved formations and their variability. Geomechanical parameters are one of the main issues in the underground works design. In the initial stages, the available information about the rock masses characteristics is scarce. As the project advances to other stages more and more information from different sources becomes available and can be used for updating the geomechanical model. Bayesian methodologies use probability as the main tool to deal with uncertainty and manage to reduce it using new data via the Bayes theorem. In this work, a part of a developed Bayesian framework to the updating of the deformability modulus (E) in an underground structure is presented. Assuming E as a random variable, data from LFJ tests is used to obtain a posterior and less uncertain distribution of E. This approach led to good results and considerable uncertainty reduction and increased reliability. The developed Bayesian framework constitutes a rational and structured way of dealing with data with different sources and uncertainty levels.